Vpliv umetno pospešenega staranja na lastnosti površinskih premazov na nemodificiranem in na modificiranem lesu - Tomažič, Miro (Zbornik gozdarstva in lesarstva, 2004)
Due to its increased dimensional stability, modified wood is suited for outside applications. Because the systems "exterior surface coatings - modified wood" have not been studied thoroughly up to now, the aim of our workwas to investigate some properties of exterior finishes on thermally modified pine wood and on some other wooden substrates. We carried out artificial accelerated aging of unpainted and painted samples and considered the influence of aging procedure on some properties of the coatings like adhesion, colour, gloss, wettability and water-vapour and liquid water permeability. The results showed that the system "thermally modified pine wood- surface coating" is comparable to conventional systems "non-modified wood - surface coating".
Keywords: lastnosti; modificiran les; premazi; umetno staranje